Concepts, Terminology, and Innovations in Follicular Unit Excision Hair Restoration Surgery - Gupta, Aditya K.; Polla Ravi, Shruthi (Facial Plastic Surgery, 2023)
Follicular unit excision (FUE) has emerged as the preferred method for hair transplants. Standardized terms and definitions established by members of the International Society of Hair Restoration Surgery and prominent hair restoration surgeons have become the standard, enabling effective knowledge sharing. This chapter provides an overview of the terminology relating to the field.The historical evolution of FUE and its pivotal role in modern hair transplantation is summarized. Anatomical terminology and graft-related definitions follow, providing insights into the scalp's complex structures and graft characteristics. The subsequent sections detail the terminology associated with graft excision and extraction, shedding light on the precise techniques and procedures employed. An exploration of various FUE techniques and the evolving landscape of FUE devices underscores the continual refinement of hair restoration practices. The chapter proceeds to discuss the “safe'” scalp donor zones, donor assessment terminology, and elements in identifying the optimal donor area for a successful FUE procedure. Additionally, punch dynamics and technique characteristics are examined, emphasizing their pivotal role in achieving superior FUE outcomes. The chapter concludes by discussing the classification of punches and graft evaluation terms, offering insights into the tools, and criteria used to assess graft quality and viability.
Keywords: follicular unit excision; hair restoration; hair transplant; FUE terminology